A case of Hypomyopathic Dermatomyositis which subsequently developed to overt Myositis with ILD - Sharma, Prayush; Datta, Abhijit; Hossain, Mohammed Zakir (Nepalese Respiratory Journal, 2022)
Dermatomyositis (DM) is an inflammatory myositis. Clinically amyopathic dermatomyositis (CADM) and hypomyopathic dermatomyositis (HDM) are rare forms of DM in which skin manifestations are present with no and minimal clinical and laboratory evidence of myositis respectively. A common complication of CADM/HDM is interstitial lung disease (ILD), with the most common histopathologic variant of non-specific interstitial pneumonia (NSIP). This case highlights the development of ILD and severe muscle weakness, including proximal limb muscles, muscles of respiration and muscles of deglutition in a patient with previous diagnosis of hypomyopathic dermatomyositis.